PENGARUH PANHISTEREKTOMI TERHADAP RETENSI KALSIUM DAN FOSFOR TIKUS SPRAGUE DAWLEY YANG DIBERI PAKAN KEDELAI SELAMA EMPAT MINGGU - Hartiningsih .; Agus Irwanto; Rosana Anita Sari; Devita Anggraini (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2008)
The objective ofthe current research was to study the effect of panhisterectomy on calcium and phosphorretention in Sprague Dawley rats fed with soybean for four weeks. Ten female Sprague Dawley rats, sixweeks of age were randomly divided into two groups (control and panhisterectomized group) of five each. Ateight weeks of age, the rats ofpanhisterectomized group were panhisterectomized. At 12 weeks of age, theywere placed into individual metabolic cages for balance study. Every morning, from day four to eight of thebalance study, the left-over feed was collected for calcium and phosphor analyses. Urine and fecal sampleswere also collected at the same time. The results of the research showed that calcium and phosphor retentionswere significantly reduced (P